Study on effect of geometry on performance of pulse detonation rocket engines (Xibei Gongye Daxue Xuebao, 2021)
In order to investigate the effect of the geometry on the performance of pulse detonation rocket engines under valveless self-adaptive working mode, the multi-cycle experiment was carried out on the pulse detonation rocket engines with different mixing sections and obstacles, while the operating frequency was 20 Hz. Gasoline was utilized as fuel, and oxygen-enriched air as oxidizer. Experimental results indicate that the DDT distance and DDT time of PDRE can be shortened by using the mixing section of gradual-expansion structure. The effect of the spiraling grooves and annular grooves on the DDT process is weak. The mixture-based specific impulse of the mixing section with gradual-expansion structure is 4.2%-7.2% lower than that of the mixing section with sudden-expansion structure. The mixture-based specific impulse of PDRE with sudden-expansion structure and Shchelkin spirals is the largest, about 116.4 s.